Goal! [videorecording (DVD)] : the dream begins - Cannon, Danny; Becker, Kuno; Dillane, Stephen, 1956-; Friel, Anna, 1976- (Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 2006)
Santiago Munez, an immigrant from Los Angeles, is given the chance to go to England to pursue his dream of becoming a professional soccer player. This underdog must prove he has the talent, passion, and determination to triumph against all odds.